Perspektif Mahasiswa Mengenai Nilai Konseling Multikultural : Studi Kasus Dimensi Religiusitas dan Orientasi Seksual - Nina Fitriyani; Dini Chairunnisa; Oktafiana Kiranida; Anisa Melamita; Agus Sukirno (Al-Shifa Jurnal Bimbingan Konseling Islam, 2026)
The multicultural counseling course plays an important role in the process of developing culturally competent practitioners, yet only a small number understand how students themselves perceive the benefits of the multicultural counseling course experience. Previous research has only focused on general outcomes related to the multicultural competence of counselors, with limited attention to the subjective perspectives of students who undergo training for one semester. This study aims to explore how Islamic guidance and counseling students conceptualize the benefits of multicultural counseling training over one semester, identifying students' understanding that shapes their learning focus and engagement with the course content. This research involves five undergraduate students in their sixth semester as subjects, using interviews to analyze students' perspectives in identifying shared subjective viewpoints that illustrate different learning preferences and interpretations regarding the value of multicultural counseling training. The results of this study indicate that students understand multicultural counseling as an effort to appreciate the differences in clients' identities and values, although the level of understanding varies. Practical-based learning experiences (case discussions, role play, field practice) are considered more effective than theory alone. Religious issues are viewed as an important factor in counseling; students recognize the need for professionalism in dealing with differences in beliefs. Issues of sexual orientation remain a significant challenge, but students are beginning to develop empathetic and non-judgmental attitudes. Multicultural counseling training provides benefits such as openness, empathy, confidence, and readiness to face a pluralistic society.